2007
DOI: 10.1073/pnas.0709326104
|View full text |Cite
|
Sign up to set email alerts
|

A role for DNA-mediated charge transport in regulating p53: Oxidation of the DNA-bound protein from a distance

Abstract: Charge transport (CT) through the DNA base pairs provides a means to promote redox reactions at a remote site and potentially to effect signaling between molecules bound to DNA. Here we describe the oxidation of a cell-cycle regulatory protein, p53, from a distance through DNA-mediated CT. A consensus p53 binding site as well as three DNA promoters regulated by p53 were synthesized containing a tethered DNA photooxidant, anthraquinone. Photoinduced oxidation of the protein occurs from a distance; introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 34 publications
1
67
0
1
Order By: Relevance
“…There are many oxidants in the cellular milieu, and the level of oxidative stress will govern the proportion of oxidized protein. Indeed, we have shown that these proteins (22) and others (27) can be oxidized by guanine radicals, the first genomic signal of oxidative stress (28), via DNA-mediated CT.…”
Section: Resultsmentioning
confidence: 99%
“…There are many oxidants in the cellular milieu, and the level of oxidative stress will govern the proportion of oxidized protein. Indeed, we have shown that these proteins (22) and others (27) can be oxidized by guanine radicals, the first genomic signal of oxidative stress (28), via DNA-mediated CT.…”
Section: Resultsmentioning
confidence: 99%
“…3A, B and data not shown) oxidation of cellular thiols should be involved. TP53 is one of the multiple cellular targets regulated by thiol modification 34,35 and we have previously observed a significant role of TP53 of dormancy. 29 However, TP53 alone cannot account for the importance of the redox imbalance since its impact on the number of dormant cells is only modest.…”
Section: Bmp4 (mentioning
confidence: 86%
“…Indeed, XPD may utilize DNA-mediated CT to signal its presence and perhaps to "call off" other proteins from other repair pathways. Various DNA-binding proteins, such as those involved in repair and other DNA transactions, have been found to contain iron-sulfur domains and other redox cofactors (50)(51)(52)(53). DNAmediated signaling among DNA-binding proteins that are involved in maintaining the integrity of the genome allows a coordination of repair, transcription, and replication processes.…”
Section: Discussionmentioning
confidence: 99%